Typifying scientific output - Erlend Kirkeng Jørgensen (Danish Journal of Archaeology, 2015)
This article presents the results of a bibliometric analysis conducted on all original research papers published in six high-ranking archaeological journals between 2009 and 2013, consisting of 926 papers. The purpose is to identify the general features characterizing the output of archaeological publishing within the given time frame and to discuss the results in light of the science/humanities divide of archaeology. It expands previous work, covering not just scientific or humanistic parts of archaeology, but sub-disciplinary niches across the science/humanities-spectrum. Significant differences are identified amongst the journals on an array of parameters, including journal statistics, citation network, thematic distribution, the application of methods and the direction of relevance to other sub-fields. Most significantly, established correlations of academic publishing are for the first time identified in archaeology, regarding the structure of citation networks, the connectedness of high-ranking journals and how specific affiliations to either side of the science/humanities divide affect publishing. In the end, these results are taken to represent a sub-optimal division of labor between archaeological sub-fields, tentatively explained by the continued relevance of the science/humanities divide in archaeology, by providing diverse epistemic underpinnings.